STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF COLLABORATIVE REASONING DISCUSSIONS (CR) (English Education Journal, 2015)
The present study was a part of larger research aimed at investigating the students’ perception on the implementation of collaborative reasoning discussions (CR) to improve their participation in English as a Foreign Language (EFL) speaking class. This study was qualitative study under action research approach conducted in a single classroom consisting of 21 undergraduate students of Economic Faculty majoring management. The data were gathered through observations and open-ended questionnaires during three cycles. The collected data were further analyzed using inductive analysis. The results indicated that 100% students agreed that CR provided them more chances to participate during the teaching and learning process. Moreover, they also stated besides giving them more chances to participate, CR brought them other benefits such as developing their critical thinking and collaborative skill, and increasing their motivation in learning English. In conclusion, the students had positive perception on the implementation of CR in their EFL speaking class.